2007
DOI: 10.1002/jts.20256
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiologic approach to the development of early trauma focused intervention

Abstract: Early, trauma-focused intervention development has emphasized unidirectional trajectories that begin with basic research and efficacy trials followed later by effectiveness and dissemination studies. In this article, the authors present methods derived from social and clinical epidemiology that constitute foundational research in the development of early trauma-focused intervention. They also describe how population-based practice research may serve to feed back and inform what has been conceptualized as earli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 68 publications
1
37
0
Order By: Relevance
“…For example in psychopharmacologic research, the process moves from lab research where a substance is produce and then first tested in animals, to efficacy research where treatment under highly controlled clinical conditions is investigated, perhaps eventually leading to effectiveness research , which evaluates a treatment under real world conditions, and to dissemination , which aims to put the treatment into use in different settings (Zatzick & Galea, 2007). …”
Section: Using Innovativemental Health Services Research Strategies Tmentioning
confidence: 99%
See 1 more Smart Citation
“…For example in psychopharmacologic research, the process moves from lab research where a substance is produce and then first tested in animals, to efficacy research where treatment under highly controlled clinical conditions is investigated, perhaps eventually leading to effectiveness research , which evaluates a treatment under real world conditions, and to dissemination , which aims to put the treatment into use in different settings (Zatzick & Galea, 2007). …”
Section: Using Innovativemental Health Services Research Strategies Tmentioning
confidence: 99%
“…This approach has contributed to clinical research intervention development. For example, Zatzick and Galea (2007) have written about the role of epidemiology in contributing to the development of early, trauma-focused interventions, which is an appropriate concern for refugee interventions. Given that trauma mental health outcomes may be due not only to trauma exposure, but to preexisting or comorbid psychiatric or health conditions, there is a role for population based studies to investigate the prevalence of mood, anxiety, or substance abuse comorbidities.…”
Section: Using Innovativemental Health Services Research Strategies Tmentioning
confidence: 99%
“…Recent commentary has argued that clinical epidemiological investigation, by systematically capturing patient, provider, and organizational level contextual factors, may be a key foundational science for the development of feasibly delivered early trauma-focused screening and intervention procedures (Zatzick & Galea, 2007). The current investigation used clinical epidemiological methods to explore the spectrum of ethnic and racial diversity and associated posttraumatic symptomatic responses in a representative sample of acutely injured trauma survivors.…”
mentioning
confidence: 99%
“…Another possible explanation for a protective effect of opiates on the development of PTSD may be the dampening of pain responses. Studies showed that pain may contribute to the development and maintenance of PTSD symptoms [42,66,67]. The administration of opiate analgesics to injury patients at our trauma center is mainly guided by the level of reported or expected pain by a patient or the medical staff.…”
Section: Discussionmentioning
confidence: 99%